FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN CARPAL TUNNEL SYNDROME (CTS) PADA SUPIR ANGKOT DI LUBUK PAKAM - Irmayani Irmayani; Anggi Isnani Parinduri; Sri Melda Bangun; Lismawati Lismawati (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2021)
Carpal Tunnel Syndrome (CTS) is a condition that affects the hands and fingers. Carpal Tunnel Syndrome (CTS) can cause symptoms in the form of tingling, pain, burning, or numbness in the fingers and hands. Complaints of Carpal Tunnel Syndrome (CTS) cause losses due to the work done. Complaints of Carpal Tunnel Syndrome (CTS) can be caused by several factors including work attitude, length of work and work period. This study aims to identify the factors associated with complaints of Carpal Tunnel Syndrome (CTS) in public transportation drivers in Lubuk Pakam. This study uses an analytical survey with a cross sectional approach. The sample in this study was public transportation drivers in Lubuk Pakam as many as 32 respondents with purposive sampling method using the chi square test with a 95% confidence level = (0.05). The results showed that there was a relationship between work attitudes (P = 0.042< (0.05), length of work (P = 0.036 < (0.05), work period (P = 0.034< (0.05)) with complaints of Carpal Tunnel Syndrome (CTS).The advice that can be given is that angkot drivers in Lubuk Pakam take regular breaks of 15-20 minutes by stretching the wrist to reduce the risk of Carpal Tunnel Syndrome (CTS) complaints.